Pathology of severe urolithiasis in a flock of egg-laying hens - Lopes, Marcelo C.; Fonseca, Clarissa S.; Amaral, Camila I.; Saraiva, Luis H.; Oliveira, Letícia B.; Silva, Dayse H. L. da; Moreira, Matheus V. L.; Silva, Fabrício J. M. da; Armour, Natalie K.; Ecco, Roselene (Brazilian Journal of Veterinary Pathology, 2021)
Fourteen, 31-week-old Lohmann white layers from a flock of 30,000 chickens had a history of apathy, and a drop in eggproduction. Clinical signs were observed in approximately 40% of the flock, and lasted for three months. Fourteen hens wereeuthanized for post-mortem examinations. Macroscopic findings included marked atrophy and loss of renal lobes along withcompensatory renal hypertrophy of the contralateral lobe. Ureters were markedly dilated and filled with mucus and/or with moldedwhite to yellow-grey uroliths that obliterated the lumen. At histopathology, the uroliths inside ureters and tubules were composedof concentrically arranged mineralized concretions, as well as urates associated with heterophilic infiltrations and epithelialhyperplasia. Renal parenchyma adjacent to obstructed ureters was compressed with tubules replaced by fibrous tissue. Multifocalinterstitial lymphocytic nephritis, proteinuria and membranoproliferative glomerulonephritis were also found. Heterophilic andcaseous ureteritis associated with numerous Gram-positive coccoid bacteria occurred in three chickens. Immunohistochemistryfor avian coronavirus was negative. This negative result along with the case history indicated that water restriction was the mostlikely cause of mortality. This condition resulted in significant economic loss for this farmer.